2004
DOI: 10.1097/00126334-200406010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8/Kaposi Sarcoma Herpesvirus Cell Association During Evolution of Kaposi Sarcoma

Abstract: Kaposi sarcoma (KS) is associated with a herpesvirus (HHV-8/KSHV), which expresses a latency-associated nuclear antigen (LANA). The histopathology of KS is characterized by angiogenesis, inflammatory cells, and the development of CD34+ tumor spindle cells (SCs). However, the cellular basis for the recruitment and dissemination of HHV-8 during the development of KS lesions is not clear. Twenty-nine KS biopsies with AIDS (AKS, n=22) and without HIV infection (endemic KS or EKS, n=7) were immunostained by a tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
1
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 31 publications
9
22
1
3
Order By: Relevance
“…Second, KSHV-infected spindle cells do not exhibit enhanced proliferation in KS lesions, but on the contrary, show significantly reduced proliferation rates as compared to uninfected cells (Kaaya et al, 2000;Kaaya et al, 1995;Köster et al, 1996). In this context, Pyakurel and colleagues showed that only a small fraction (up to 5%) of all latency-associated nuclear antigen (LANA)-1-positive KS spindle cells proliferate in KS lesions (Pyakurel et al, 2004). Our data confirmed these findings (Lorenz, 2007).…”
Section: Ks: Reactive Hyperplasia Rather Than True Malignancy?supporting
confidence: 86%
“…Second, KSHV-infected spindle cells do not exhibit enhanced proliferation in KS lesions, but on the contrary, show significantly reduced proliferation rates as compared to uninfected cells (Kaaya et al, 2000;Kaaya et al, 1995;Köster et al, 1996). In this context, Pyakurel and colleagues showed that only a small fraction (up to 5%) of all latency-associated nuclear antigen (LANA)-1-positive KS spindle cells proliferate in KS lesions (Pyakurel et al, 2004). Our data confirmed these findings (Lorenz, 2007).…”
Section: Ks: Reactive Hyperplasia Rather Than True Malignancy?supporting
confidence: 86%
“…Previous investigations have demonstrated KSHV infection in circulating monocyte/macrophages and B lymphocytes of KS patients, suggesting that these cells may participate in the dissemination of viral infection in vivo. [7][8][9] KSHV can establish limited infections in a variety of cells in vitro, including human B cells, endothelial cells, epithelial cells, fibroblast cells, mesenchymal stem cells, dendritic cells, and macrophages. [4][5][6][10][11][12][13][14][15][16] In vivo, KSHV infection has been localized to human B cells, macrophages, keratinocytes, endothelial cells, and epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Como descrito anteriormente, a lesão de SK independentemente da forma clínico-epidemiológica está associada à proliferação de células fusiformes, as quais são na maioria infectadas pelo HHV-8 (Pyakurel et al, 2004 (Stürzl et al, 1992), assim como, marcadores específicos de vasos linfáticos (VEGFR-3 e D2-40) (Weninger et al, 1999 (Hong et al, 2004;Carrol et al, 2004).…”
Section: Sarcoma De Kaposi: Inflamação E/ou Tumor?unclassified
“…A participação dessas células na patogênese do SK tem sido demonstrada por outros autores (Pyakurel et al, 2004;Hussein, 2007), (Donaghy et al, 2001;Pacanowski et al, 2001), outros demonstraram que essa diminuição de populações celulares de origem distinta não ocorre concomitantemente (Grassi et al, 1999;Soumelis et al, 2001).…”
Section: Tese De Doutorado -Fernanda Guedes Luizunclassified
See 1 more Smart Citation